Meningkatkan Perkembangan Bahasa Keaksaraan Anak Usia 5–6 Tahun Melalui Media Ular Tangga Kreasi - Salsavira, A’inur Rofida; Sari, Anisa Yunita (Universitas Narotama, 2025)
This study uses a quantitative research approach with a pre-experimental research type using a one group pre-test and post-test design. The research subjects were all children in group B at TK Dharma Wanita Persatuan Medaeng Sidoarjo, totaling 18 children. The data collection methods used were observation using evaluation tools in the form of observation sheets and documentation, as well as performance tests. Data processing calculations were assisted using SPSS version 25. Based on the results of the paired samples test using SPSS version 25, it shows that the research results obtained a Sig. (2-tailed) value of 0.000 <0.05. Therefore, it can be concluded that there is an influence of using creative snakes and ladders media on the literacy language development of children aged 5-6 years at TK Dharma Wanita Persatuan Medaeng Sidoarjo. Keywords: Language Literacy, Early Childhood Education, Literacy Language Development, Snakes and Ladders Game, Pre-Test and Post-Test Design